A comparative proteomic study on the effects of metal pollution in oysters Crassostrea hongkongensis. Issue 1 (15th November 2016) - Xu, Lanlan; Ji, Chenglong; Wu, Huifeng; Tan, Qiaoguo; Wang, Wen-Xiong
Abstract: The metal pollution has posed great risk on the coastal organisms along the Jiulongjiang Estuary in South China. In this work, two-dimensional electrophoresis-based proteomics was applied to the oysters Crassostrea hongkongensis from metal pollution sites to characterize the proteomic responses to metal pollution. Metal accumulation and proteomic responses indicated that the oysters from BJ site were more severely contaminated than those from FG site. Compared with those oyster samples from the clean site (JZ), metal pollution induced cellular injuries, oxidative and immune stresses in oyster heapatopancreas from both BJ and FG sites via differential metabolic pathways. In addition, metal pollution in BJ site induced disturbance in energy and lipid metabolisms in oysters. Results indicated that cathepsin L and ferritin GF1 might be the biomarkers of As and Fe in oyster C. hongkongensis, respectively. This study demonstrates that proteomics is a useful tool for investigating biological effects induced by metal pollution. Highlights: Metal pollutions caused differential responses in oysters from Baijiao and Fugong. Metal pollutions induced oxidative and immune stresses in oysters. Cathepsin L might be used as a biomarker of As in oysters . Ferritin GF1 might be the biomarker of Fe in oysters . Proteomics is useful to study the effects induced by metal pollutions in organisms.